2000
DOI: 10.4049/jimmunol.164.6.3292
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines Fail to Up-Regulate β1 Integrin-Dependent Adhesion in Human Th2 T Lymphocytes

Abstract: Th1 and Th2 cells are functionally distinct subsets of CD4+ T lymphocytes whose tissue-specific homing to sites of inflammation is regulated in part by the differential expression of P- and E-selectin ligands and selected chemokine receptors. Here we investigated the expression and function of β1 integrins in Th1 and Th2 cells polarized in vitro. Th1 lymphocytes adhere transiently to the extracellular matrix ligands laminin 1 and fibronectin in response to chemokines such as RANTES and stromal cell-derived fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…Indeed, we found that antibody-induced crosslinking of CD44 resulted in a 2.3-fold increase in the binding of Th1 cells to recombinant ICAM-1, confirming that CD44-derived signaling modulates T-cell adhesive properties ( Figure 4C). This modulation is comparable to that induced after crosslinking of PSGL-1 37 or by chemokines, 38 suggesting a cooperation of selectins and chemokines for Th1 cell arrest.…”
Section: Cd44 Is An E-selectin Ligand On T Cells 2441supporting
confidence: 58%
“…Indeed, we found that antibody-induced crosslinking of CD44 resulted in a 2.3-fold increase in the binding of Th1 cells to recombinant ICAM-1, confirming that CD44-derived signaling modulates T-cell adhesive properties ( Figure 4C). This modulation is comparable to that induced after crosslinking of PSGL-1 37 or by chemokines, 38 suggesting a cooperation of selectins and chemokines for Th1 cell arrest.…”
Section: Cd44 Is An E-selectin Ligand On T Cells 2441supporting
confidence: 58%
“…This suggests that clustering of integrins is at least partially dependent on the presence of a suitable integrin ligand. Although differential regulation of ␤ 1 vs ␤ 2 integrin function in T cells by chemokines is possible under some conditions (35,36), our experiments demonstrated similar clustering of ␣ 1 and ␤ 2 integrins on the cell surface in response to CCL20 as long as both VCAM-1 and ICAM-1, respectively, were immobilized on the plate.…”
Section: Discussionmentioning
confidence: 56%
“…In addition to PSGL-1, certain integrins likely to be important for passage across the endothelium have also been reported to be differentially expressed on Th1 and Th2 cells (72,73). We have shown ␣ L ␤ 2 (LFA-1), a receptor for ICAM-1, at higher levels on IFN-␥-producing, Th1-like cells.…”
Section: Discussionmentioning
confidence: 68%